Makna Merokok bagi Wanita: Studi Fenomenologi pada Mahasiswi Perokok - Usman, Ari (RESIPROKAL: Jurnal Riset Sosiologi Progresif Aktual, 2024)
Smoking activity is not only dominated by men. Female smoker is an existing phenomena that can be found in our daily life. Most of them are female college student. Even though they are threatened by some health risks and negative stigmas from society, female smokers keep doing their habit. This phenomena becomes interesting to explore that we may have deeper understanding about the meaning of smoking from the female smoker perspective. This study uses qualitative method with phenomenology approach. Data gain by: in-depth interview, observation, and literature study. The result shows that female smoker perceives smoking activity as: breathing exercise that bring calm and clarity of mind, an emotional reducer that helps relieve anger or sadness, a self-protection camouflage as a tough woman. Nevertheless informant also thinks that smoking could be harmful because of the health risk and stereotype from others. Based on analysis using Cognitive Dissonance Theory, the three meanings are the informant's efforts to minimize the dissonance between one cognitive element that she already knows about the risks of smoking for women and the cognitive element of the informant as an active smoker.